Faktor yang Berhubungan dengan Stres Kerja pada Perawat di Rumah Sakit Umum Daerah Sayang Rakyat Makassar - Lisdha Ardiyany Ilyas; Muhammad Rum Rahim; Awaluddin Awaluddin (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The development of the world of work is greatly improved with various types of occupational professions, ranging from light work to work that drains the mind and also energy in addition, workers from any profession must have felt fatigue when they carry out work, and it can trigger work stress on someone who arises from several factors in the workplace so that the quality of their work is not productive. The study aims to determine the relationship between age, workload, mental demands, social support for work stress in nurses at RSUD Sayang Rakyat Makassar. The cross sectional study was conducted. The research will be conducted at RSUD Sayang Rakyat Makassar in February until March 2020. The population in this study is all nurses of RSUD Sayang Rakyat Makassar totaling 99 people. Analysis of the data used univariate and bivariate analysis. The results showed that as many as 15.2% experienced work stress and those without work stress were 84.8%. There is no relationship between age and value (p=0.421). There is no relationship between workload (p=0,000) and social support (p=0.001), mental demands (p=0,000) have a relationship with nurses at RSUD Sayang Rakyat Makassar. This research suggests evaluating nurses work descriptions and effective communication routinely every briefing before work. It is expected that activities outside of work such as recreation or in the form of entertainment.